Aplicativos móveis para praticar a leitura social: análise e avaliaçao de recursos úteis - Dantas, Taísa (2018)
This article aims to understand how mobile applications can be used to assist readers during social reading practice, through the analysis of different available resources, their benefits, and limitations. This study has a descriptive and analytical qualitative methodology approach, based on studies focused on the evaluation of electronic resources. In this case, ten reading applications available on Android and iOS operating systems designed for both tablet and smartphone reading, were evaluated. Was possible to conclude that mobile applications are efficient software to encourage the reader to carry out activities planned within the modality of social reading. Especially in what corresponds to the practice of active reading. On the other hand, was verified that for sharing the reading practice, until now, most of the evaluated applications hold weaknesses. Mainly, to encourage the reader to interact with other readers. The tools are limited to sharing through non-specialized platforms within the context of the book and outside of the application